2006
DOI: 10.19182/remvt.9950
|View full text |Cite
|
Sign up to set email alerts
|

Parasitisme interne du mouton de race Ouled Djellal en zone semi-aride d’Algérie

Abstract: Une étude du parasitisme interne a été réalisée chez des ovins de race Ouled Djellal infestés naturellement dans une région semi-aride d’Algérie (Tiaret). Des coproscopies effectuées pendant l’année 2004 sur 423 ovins ont révélé un taux global d’infestation de 78,9 p. 100 et ont permis d’identifier des cestodes (Moniezia spp., Avitellina sp.), des coccidies (Eimeria spp.) et des nématodes dont des strongles respiratoires (Dictyocaulus sp., Muellerius sp., Protostrongylus sp.). Le parasitisme a été saisonnier p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In a study carried out in Tiaret (western Algeria) on the Ouled Djellal breed, Boulkaboul and Moulaye (2006) reported the presence of 334 heads infested with intestinal cestodes, out of a total of 423 heads. Another study on internal parasitism was carried out by Saidi et al (2009) in sheep of the Rembi breed in a steppe region of Algeria (Ain D'hab) showed a low prevalence of infestation by intestinal cestodes (Moniezia sp) compared to other internal parasites.…”
Section: Prevalence Of Infestation According To Host Racementioning
confidence: 99%
See 3 more Smart Citations
“…In a study carried out in Tiaret (western Algeria) on the Ouled Djellal breed, Boulkaboul and Moulaye (2006) reported the presence of 334 heads infested with intestinal cestodes, out of a total of 423 heads. Another study on internal parasitism was carried out by Saidi et al (2009) in sheep of the Rembi breed in a steppe region of Algeria (Ain D'hab) showed a low prevalence of infestation by intestinal cestodes (Moniezia sp) compared to other internal parasites.…”
Section: Prevalence Of Infestation According To Host Racementioning
confidence: 99%
“…The latter is found at a prevalence of 22% in females and 19% in males for sheep, and 18% in females and 38% in males for goats. Boulkaboul et al (2006) reported that it was approximately three times more frequent, and that Moniezia benedeni is less common observed more often in cattle than sheep. Chartier et al (2000) stated that the distribution of species is not uniform although Anoplocephalidosis is a cosmopolitan affection, in addition these species are more likely to be seen in warm and dry regions.…”
Section: Prevalence Of Infestation According To Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Algerian Coastal Region characterized by a Mediterranean climate, contrary to the steppe area with a semiarid climate [5,6,7], the internal parasitism of sheep is not well documented. Its study mainly involves surveys in slaughterhouses [8].…”
Section: Introductionmentioning
confidence: 99%